2015
DOI: 10.1002/qua.24944
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of proton exchange in a model phosphonic acid-functionalized polymer

Abstract: The dynamics and mechanism of proton exchange in phosphonic acid-functionalized polymers were studied using poly(vinyl-phosphonic acid) (PVPA) as a model system along with quantum chemical calculations and Born-Oppenheimer molecular dynamics (BOMD) simulations at the B3LYP/TZVP level as model calculations. This theoretical study began with searching for the smallest, most active polymer segments and their intermediate conformations which could be involved in the local proton-exchange process. The B3LYP/TZVP re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Our theoretical studies of the Grotthuss mechanism also revealed that the dynamics of proton transfer can be affected by the motions of aromatic rings, e.g. in phosphonic acid-functionalized polymer (poly(vinyl-phosphonic acid)) [ 13 ] and H 3 PO 4 -doped imidazole (Im) systems [ 14 ]; these motions can be compared with the polymer segmental motion in [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our theoretical studies of the Grotthuss mechanism also revealed that the dynamics of proton transfer can be affected by the motions of aromatic rings, e.g. in phosphonic acid-functionalized polymer (poly(vinyl-phosphonic acid)) [ 13 ] and H 3 PO 4 -doped imidazole (Im) systems [ 14 ]; these motions can be compared with the polymer segmental motion in [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the FDC1 enzyme is exceedingly large for high-level ab initio methods and because our previous studies showed that the mechanisms for proton transfer in heterocyclic aromatic systems can be studied reasonably well using the B3LYP method with the DZP basis set, [11][12][13] the B3LYP/DZP method was used in this study; our benchmark calculations on bifunctional proton transfers in poly(benzimidazole) (PBI) H-bond systems 14 conrmed that the B3LYP/DZP method yields approximately the same equilibrium and transition structures and relative interaction energies as the B3LYP/TZP method with reasonable computational resources. In this study, the model molecular clusters that were hypothesized in ref.…”
Section: Quantum Chemical Methodsmentioning
confidence: 99%